The Significance of the Great Contribution of Modern Women Writers to Literature and Cultural Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
There is no doubt that the modern literary scene is enriched with talented women writers who make a significant contribution to the world of words and art. Their unique view of life, inner world, socio-cultural phenomena brings their works to the attention of a wide readership. In this article, we will focus on the important role of women writers in modern literature and their importance for society and culture.